Profiling mycobacterial communities in pulmonary nontuberculous mycobacterial disease - Cowman,SA; James,P; Wilson,R; Cookson,WOC; Moffatt,MF; Loebinger,MR (PLoS ONE, 2018)
The diagnosis of pulmonary non-tuberculous mycobacterial disease (pNTM) is dependent on the isolation of NTM in culture, which is prone to overgrowth and contamination and may not capture the diversity of mycobacteria present, including rare or unidentified species. This study aimed to develop a culture independent method of detecting and identifying mycobacteria from sputum samples using partial sequencing of the hsp65 gene. DNA was extracted from sputum samples from subjects with pNTM and disease controls. Multiplexed partial sequencing of the hsp65 gene was performed using the Illumina MiSeq and custom primers. A reference database of hsp65 sequences was created for taxonomy assignment. Sequencing results were obtained from 42 subjects (31 cases, 11 controls). Mycobacterial sequences were identified in all subjects. In 90.5% of samples more than one species was found (median 5.5). The species isolated in culture was detected by sequencing in 81% of subjects and was the most abundant species in 62%. The sequencing of NTM from clinical samples reveals a far greater diversity than conventional culture and suggests NTM are present as communities rather than a single species. NTM were found to be present even in the absence of isolation in culture or clinical disease.